EFEKTIVITAS SPRAY GEL EKSTRAK CALENDULA OFFICINALIS (TAGETAS ERECTA L) TERHADAP PENYEMBUHAN LUKA PERINIUM PADA IBU NIFAS - Novita, Novita; Rahayu, Sri; Supriyadi, Supriyadi (Poltekkes Kemenkes Bandung, 2024)
Perineal wounds in postpartum mothers will become moist because they are passed through by lochia and their presence close to the anus will be a fertile place for the growth of bacteria that can cause infection. Efforts to prevent infection and accelerate healing require treatment, one of the treatments that can be done is by administering Calendula officinalis extract gel spray. The purpose of this study was to prove that administering Calendula officinalis extract gel spray is effective in healing perineal wounds in postpartum mothers. This study is a true experimental study with a pre-test post-test with control group design. The technique used was random sampling, with 34 respondents divided into 2 groups, the intervention group was given Calendula officinalis extract gel spray and the control group was given Calendula officinalis extract gel measured using the REEDA scale. The test used was the Mann Whitney test. The intervention group of Calendula officinalis extract spray gel was effective for healing perineal wounds in postpartum mothers with an average value of 7.44 in the pre-test and 0.03 in post-test III, while in the control group, with p-value pre test and post test III intervention and control groups is 0.000. Calendula officinalis extract gel had an average value of 7.47 in the pre-test and 0.09 in post-test III. Administration of Calendula officinalis extract spray gel had an effect on healing perineal wounds in postpartum mothers based on the REEDA score.